2011
DOI: 10.1002/cncr.26115
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life care in Medicare beneficiaries dying with pancreatic cancer

Abstract: BACKGROUND Our goal was to characterize hospice enrollment and aggressiveness of care for pancreatic cancer patients at the end of life. METHODS We used Surveillance, Epidemiology, and End Results (SEER) and linked Medicare claims data (1992–2006) to identify patients with pancreatic cancer who had died (n= 22,818). We evaluated hospice use, hospice enrollment ≥4 weeks before death, and aggressiveness of care as measured by receipt of chemotherapy, acute care hospitalization, and intensive care unit (ICU) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 35 publications
5
53
1
Order By: Relevance
“…18,19,43 The proportion of costs attributable to inpatient care unrelated to cancer-directed procedures was highest for those diagnosed with distant disease, possibly due to extensive hospitalization over a limited time period. 8,41,44 In addition, inpatient costs were relatively stable over time, although we did observe an increase in costs of outpatient care and physician services. In recent years, across a range of cancer types and stages of disease, treatment costs have shifted away from the inpatient setting toward outpatient care.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…18,19,43 The proportion of costs attributable to inpatient care unrelated to cancer-directed procedures was highest for those diagnosed with distant disease, possibly due to extensive hospitalization over a limited time period. 8,41,44 In addition, inpatient costs were relatively stable over time, although we did observe an increase in costs of outpatient care and physician services. In recent years, across a range of cancer types and stages of disease, treatment costs have shifted away from the inpatient setting toward outpatient care.…”
Section: Discussionmentioning
confidence: 62%
“…Recent evidence suggests that patients presenting with distant or unresectable locoregional pancreatic cancer are more likely to receive chemotherapy within the last month of life. 44 Average chemotherapy costs were highest in patients with resectable locoregional disease, who may receive chemotherapy in the adjuvant setting and later with palliative intent at the time of disease progression. Although there has been a steady increase in adjuvant chemotherapy use and a growing interest in neoadjuvant therapy for the resected population, we did not observe any significant increase in the cost of chemotherapy and radiation therapy over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a population-based study of end-of-life care in pancreatic cancer patients, Sheffield et al found an increase in aggressive care in the last month of life, with an increase in ICU admission from 15.5% in 1992–1994 to 19.6% in 2004–2006 ( P < 0.0001) and an increase in receipt of chemotherapy from 8.1% to 16.4% ( P < 0.0001). [54] This suggests that aggressive care, in addition to being linked to worse quality of life for patients, and worse bereavement adjustment for their caregivers, [5558] results in increased costs with little survival benefit.…”
Section: End Of Life Care and The Role Of Hospicementioning
confidence: 99%
“…Furthermore, among patients with loco-regional disease, those who underwent resection were less likely to enroll in hospice before death, supporting the need for early discussion of palliative care and hospice care regardless of stage at diagnosis. [54]…”
Section: End Of Life Care and The Role Of Hospicementioning
confidence: 99%
“…The feasibility of claims assessment has promoted expansion of EOL evaluation to populations with specific cancer diagnoses, such as pancreatic cancer 27,28 and lung cancer, 10 and to services that have not been subject to rigorous evaluation and national endorsement, such as the use of radiation and surgery near EOL. 29 Additional claims-based studies have been conducted outside of the U.S. 4,30e33 Using modified measures based on individual institutional medical records abstraction, the American Society of Clinical Oncology's Quality Oncology Practice Initiative has found national variation and performance gaps within the U.S., with some evidence that assessment over time is associated with improvement.…”
Section: Introductionmentioning
confidence: 99%